2006
DOI: 10.1590/s0103-50532006000300017
|View full text |Cite
|
Sign up to set email alerts
|

Limonoids from andiroba oil and Cedrela fissilis and their insecticidal activity

Abstract: Nove limonóides foram isolados de Carapa guianensis e Cedrela fissilis. Entre eles, a 1,2-diidro-3β-hidroxi-7-desacetoxi-7-oxogedunina é uma substância inédita. Além disso, alguns deslocamentos químicos da xilocensina k foram corrigidos e os dados de RMN 1 H da 7-desacetilgedunina são descritos pela primeira vez na literatura. Seis dos limonóides isolados foram submetidos a ensaios com formigas Atta sexdens rubropilosa e apresentaram atividade inseticida moderada. Nine limonoids were isolated from Carapa guian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 15 publications
2
41
0
5
Order By: Relevance
“…Previous studies of C. fissilis showed the isolation of limonoids and triterpenes (Taylor, 1984;Zelnik, 1966Zelnik, , 1970Leite et al, 2005a;Ambrozin et al, 2006) and C. fruticosa has been reported to contain ent-clerodanes and labdanes diterpenoids , limonoids, steroids, sesquiterpenoids, heneicosene derivatives and one coumarin (Luo et al, 2000(Luo et al, , 2001Leite et al, 2005a,b). There are no phytochemical studies about T. ramalhoi, but several compounds have been isolated from the Trichilia genus, such as, limonoids (Cortez et al, 1992;Garcez et al, 1997;Garcez, et al, 2000;Cortez et al, 2000), lignan glycosides (Cortez et al, 1998), w-phenyl alkanoic and alkenoic acids (Pupo et al, 1996), terpenoids, steroids Pupo et al, 1996) and g-lactones (Pupo et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of C. fissilis showed the isolation of limonoids and triterpenes (Taylor, 1984;Zelnik, 1966Zelnik, , 1970Leite et al, 2005a;Ambrozin et al, 2006) and C. fruticosa has been reported to contain ent-clerodanes and labdanes diterpenoids , limonoids, steroids, sesquiterpenoids, heneicosene derivatives and one coumarin (Luo et al, 2000(Luo et al, , 2001Leite et al, 2005a,b). There are no phytochemical studies about T. ramalhoi, but several compounds have been isolated from the Trichilia genus, such as, limonoids (Cortez et al, 1992;Garcez et al, 1997;Garcez, et al, 2000;Cortez et al, 2000), lignan glycosides (Cortez et al, 1998), w-phenyl alkanoic and alkenoic acids (Pupo et al, 1996), terpenoids, steroids Pupo et al, 1996) and g-lactones (Pupo et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the repellent effect, andiroba oil showed toxic action on the third and fourth instar larvae of Aedes albopictus, A. aegypti and flies of the genus Culex (Silva et al 2004;Emerick et al 2005). Ambrozin et al (2006) observed that the oil extracted from the seeds of andiroba also presented toxic effect on the leafcutter ant Atta sexdens rubropilosa.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of this species contain high oil content of the triterpene chemical group, called limonoids (andirobin, gedunin and epoxy azadiradione). These substances are proven antifeedants to insects (Mikolajczak, 1988;Ambrozin et al, 2006). Thus it becomes extremely important to develop studies using non-residual therapies such as the andiroba oil to serve as an auxiliary tool in reducing the attack of fruit flies on fruit trees of temperate climates.…”
Section: Introductionmentioning
confidence: 99%
“…Este fato deve ser consequente da natureza química do óleo tratar-se de sesquiterpenos e diterpenos ácidos (Tappin et al 2004), que pelo processo da rota metílica clássica produziu sabão ao invés de biodiesel. O óleo de Carapa guianensis também apresenta ácidos em sua constituição (linoleico, esteárico, entre outros) (Ambrozin et al 2006;Bataglion et al 2014), mas a presença significativa de triacilglicerídeo possibilitou a obtenção do biodiesel.…”
Section: Discussionunclassified